The superoxide dismutase mimetic, tempol, blunts right ventricular hypertrophy in chronic hypoxic rats - Elmedal, Britt (2003)
1. The purpose of this study was to investigate whether a membrane-permeable superoxide dismutase mimetic, tempol, added either alone or in combination with the nitric oxide (NO) donor molsidomine, prevents the development of pulmonary hypertension (PH) in chronic hypoxic rats. 2. Chronic hypobaric hypoxia (10% oxygen) for 2 weeks increased the right ventricular systolic pressure (RVSP), right ventricle and lung wet weight. Relaxations evoked by acetylcholine (ACh) and the molsidomine metabolite SIN-1 were impaired in isolated proximal, but not distal pulmonary arteries, from chronic hypoxic rats. 3. Treatment with tempol (86 mg kg(−1) day(−1) in drinking water) normalized RVSP and reduced right ventricular hypertrophy, while systemic blood pressure, lung and liver weights, and blunted ACh relaxation of pulmonary arteries were unchanged. 4. Treatment with molsidomine (15 mg kg(−1) day(−1) in drinking water) had the same effects as tempol, except that liver weight was reduced, and potassium and U46619-evoked vasoconstrictions in pulmonary arteries were increased. Combining tempol and molsidomine did not have additional effects compared to tempol alone. ACh relaxation in pulmonary arteries was not normalized by these treatments. 5. The media to lumen diameter ratio of the pulmonary arteries was greater for the hypoxic rats compared to the normoxic rats, and was not reversed by treatment with tempol, molsidomine, or the combination of tempol and molsidomine. 6. We conclude that tempol, like molsidomine, is able to correct RVSP and reduce right ventricular weight in the rat hypoxic model. Functional and structural properties of pulmonary small arteries were little affected. The results support the possibility that superoxide dismutase mimetics may be a useful means for the treatment of PH.